Implementation For Augmentative And Alternative Communication (AAC) Tools For Rett Syndrome Individual In Activities Of Daily Living (ADL) - Maulahikmah Galinium; Timothy Aditya Sutantyo; Eka Budiarto (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Rett Syndrome occurs between one in 10000 to 15000 girls in Indonesia. In Hasan Sadikin Hospital, Bandung, Indonesia, there is a girl suffering from Rett Syndrome. Doctors in Hasan Sadikin Hospital find a lot of difficulties in communicating with the patient, since Rett Syndrome patients has little-to-no speech capabilities, and their hands often move involuntarily, especially with regards to Activities of Daily Living (ADL). Hence, a method to communicate with Rett Syndrome patient is being proposed using Augmentative and Alternative Communication (AAC) to support communication between the caregiver and the patient. Two of those methods are using gaze-tracking and head-pose. The methods tested consists of head-pose algorithm, gaze-tracking with Dlib, gaze-tracking with Haar Cascades, and EyeTribe. Each method is tested first with normal people before being tested with the patient. EyeTribe, head-pose, and gaze-tracking algorithm using Dlib achieve good results, with the best results being at 50cm distance and with high light intensity, however the Rett Syndrome patient achieves poor results when using the application, although head-pose achieves the best results in terms of determining needed ADL at around 45% accuracy. Hence, the Rett Syndrome patient needs training to use the application properly.